Inflammatory response and IgE sensitization at early age. Issue 4 (11th April 2013) - Mustonen, Kirsi; Orivuori, Laura; Keski‐Nisula, Leea; Hyvärinen, Anne; Pfefferle, Petra Ina; Riedler, Josef; Dalphin, Jean‐Charles; Genuneit, Jon; Lauener, Roger; Roduit, Caroline; Braun‐Fahrländer, Charlotte; Weber, Juliane; et al.
Abstract Background Microbial exposure may induce low‐grade inflammation at an early age and decrease the risk of allergic diseases, as suggested by the hygiene hypothesis. We examined the associations between low‐grade inflammation and the development of allergic sensitization, atopic dermatitis (AD), and asthma at the age of 4.5 yr. Methods We studied 636 children participating in the PASTURE study in Finland, Germany, Austria, France, and Switzerland. Data of environmental factors, doctor‐diagnosed AD, and asthma were collected by questionnaire. The serum high‐sensitivity C‐reactive protein (CRP) values were measured at the age of 1 yr, and serum‐specific IgE concentrations (sIgE) at the age of one and 4.5 yr. Analyses were made by logistic regression analysis. Results The risk of allergic sensitization at the age of 4.5 yr was decreased in children who had increased CRP levels at the age of 1 yr (level in the highest vs. lowest quartile: aOR 0.48, 95% CI 0.24–0.95; p = 0.014). The risk of AD and asthma was not significantly related to CRP. Conclusion The findings confirm that elevated levels of CRP at early age showed association with decreased allergic sensitization later in life. Our results suggest that poor inflammatory response could predispose for IgE sensitization.